2016
DOI: 10.1186/s12906-016-1038-8
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of ShenXiong glucose injection for acute ischemic stroke: a systematic review and GRADE approach

Abstract: BackgroundTo appraise critically whether published trials of ShenXiong glucose injection for patients with acute ischemic stroke (AIS) are of sufficient quality, and in addition to rate the quality of evidence by using the GRADE approach (grading of recommendations, assessment, development, and evaluation, GRADE).MethodsA literature search was performed in the Cochrane Library, MEDLINE, EMBASE, CBM, Chinese TCM (traditional Chinese medicine) Database, CNKI, VIP, WanFang Databases until January 2015. The limits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Shenxiong glucose injection (SGI) is a preparation containing the water extracts of Salvia miltiorrhiza Bunge and ligustrazine hydrochloride. The injection is widely used in China for the treatment of cardiovascular and cerebrovascular diseases, such as angina pectoris [ 1 , 2 ], coronary heart disease [ 3 ], myocardial infarction [ 4 , 5 ], acute cerebral infarction [ 6 , 7 ], and ischemic stroke [ 8 ]. The randomized controlled trial studies showed that the total efficiency was greater than 79% [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Shenxiong glucose injection (SGI) is a preparation containing the water extracts of Salvia miltiorrhiza Bunge and ligustrazine hydrochloride. The injection is widely used in China for the treatment of cardiovascular and cerebrovascular diseases, such as angina pectoris [ 1 , 2 ], coronary heart disease [ 3 ], myocardial infarction [ 4 , 5 ], acute cerebral infarction [ 6 , 7 ], and ischemic stroke [ 8 ]. The randomized controlled trial studies showed that the total efficiency was greater than 79% [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…SGI, consisted of two effective ingredients ligustrazine hydrochloride and tanshinol, has shown multiple effects on cerebral disease, but the cardioprotective effect and mechanisms of SGI has been rarely reported [8]. The objective of our present study is to examine whether SGI plays a protective role in AMI injury and explore its potential mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that SGI possesses protective effects on cerebral, and its potential mechanisms are involved in antiinflammation, anti-oxidation and anticoagulation [8]. And what's more, clinical applications and animal experimental studies have demonstrated that there are seldom adverse effects after administration of SGI [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher score indicates severe neurological impairment, and its minimum clinically important difference is 2 points 30,31 . The systematic reviews 32‐40 suggested that the use of Chinese herbal medicine (Table 1) in addition to conventional care and treatment in the 2 weeks after onset resulted in less neurological impairment in patients with ischemic stroke. Chinese herbal medicines that activate blood and resolve stasis were widely used, and they were often administered for 3‐30 days.…”
Section: Recommendationsmentioning
confidence: 99%